Microlearning-Based Learning Strategies to Strengthen Elementary School Students' Disciplined Character in the Digital Era - Muallipah Muallipah; Mawita Restiani; Alfiah Noviana; Suherli Kusmana (Universitas Nusantara PGRI Kediri, 2026)
This study aims to investigate the impact of microlearning-based learning strategies on the academic achievement and learning discipline of elementary school students in Natural and Social Sciences (IPAS). The study used a quantitative approach with an experimental design conducted at SDN Kartini I and SDN Kartini II. The research subjects were 65 sixty five students divided into two groups. Each group implemented the Discovery Learning and Problem-Based Learning models combined with the microlearning approach. Microlearning was presented in the form of short, structured, and varied learning materials to increase student activity and focus during the learning process. Data collection was carried out through learning outcome tests in the form of pretests and posttests, as well as observations to assess student learning discipline during learning activities. Data analysis used paired t-tests to determine differences in learning achievement before and after treatment, and Pearson correlation analysis and simple regression to examine the relationship and influence between variables. The results showed a significant difference between students' pretest and posttest scores (p < 0.05). These findings prove that the combination of microlearning with the Discovery Learning and Problem-Based Learning models is effective in improving learning outcomes. In addition, this learning strategy also has a positive impact on improving student learning discipline.